2020
DOI: 10.1002/cam4.2969
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub methylated‐CpG sites and associated genes in oral squamous cell carcinoma

Abstract: To improve personalized diagnosis and prognosis for oral squamous cell carcinoma (OSCC) by identification of hub methylated-CpG sites and associated genes, weighted gene comethylation network analysis (WGCNA) was performed to examine and identify hub modules and CpG sites correlated with OSCC. Here, WGCNA modeling yielded blue and brown comethylation modules that were significantly associated with OSCC status. Following screening of the differentially expressed genes (DEGs) from gene expression microarrays and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The presence of ACTA1 expressing fibroblasts in the prostate cancer stroma is associated with increased tumour metastatic potential [31] . In the case of oral squamous cell carcinoma, high expression of ACTA1 is associated with shorter survival ( Table 1 ) [32] . Additionally, in basal-like breast cancer, ACTA1 is a biomarker that is associated with chemoresistance ( Table 1 ) [33] .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of ACTA1 expressing fibroblasts in the prostate cancer stroma is associated with increased tumour metastatic potential [31] . In the case of oral squamous cell carcinoma, high expression of ACTA1 is associated with shorter survival ( Table 1 ) [32] . Additionally, in basal-like breast cancer, ACTA1 is a biomarker that is associated with chemoresistance ( Table 1 ) [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal DNA methylation patterns, including hypermethylation of gene promoter region which is accompanied by gene silencing, play a key role in a large number of cancers [ 18 ]. Previous research revealed that the hub-methylated sites were related the diagnosis and prognosis for OSCC by weighted gene comethylation network analysis (WGCNA) [ 19 ]. To identify samples with CIMP, patients were clustered by K-means method in our study, and the results suggested that samples with CIMP had lower survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…carcinoma (Dai et al, 2020) and pancreatic cancer (Wang et al, 2020). In regard to HCC, many studies have been conducted to identify the hub genes correlated with its progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Then, correlation analysis between these modules and different phenotypes was used to determine the molecular characteristics of the specific phenotype. To date, WGCNA has been used to explore hub genes and tumor biomarkers of many cancers, such as bladder cancer ( Jiang et al, 2020 ), prostate cancer ( Wei et al, 2020 ), oral squamous cell carcinoma ( Dai et al, 2020 ) and pancreatic cancer ( Wang et al, 2020 ). In regard to HCC, many studies have been conducted to identify the hub genes correlated with its progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%